2008
DOI: 10.1001/archinternmed.2007.59
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Preclinical Interstitial Lung Disease in Rheumatoid Arthritis

Abstract: Asymptomatic preclinical ILD, which is detectable by HRCT, may be prevalent and progressive among patients having RA. Cigarette smoking seems to be associated with preclinical ILD in patients having RA, and treatment using methotrexate may be a risk factor for progression of preclinical ILD. Quantification of alveolar proteins indicates that potential pathogenic mechanisms seem to differ in patients having RA-ILD and symptomatic RAPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
294
2
33

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(362 citation statements)
references
References 21 publications
14
294
2
33
Order By: Relevance
“…The majority of cases of RA-ILD occur in patients between the ages of 50 and 60 years. While several studies 13,[15][16][17]20 have reported smoking, male gender, and longstanding RA to be risk factors for the development of ILD, other reports 13,14,16,17,19 have not shown any significant associations. In addition, genetic associations (human leukocyte antigen B40 and ␣ 1 -antitrypsin) have been described.…”
Section: Ra-ild: Epidemiology and Clinical Presentationmentioning
confidence: 86%
See 1 more Smart Citation
“…The majority of cases of RA-ILD occur in patients between the ages of 50 and 60 years. While several studies 13,[15][16][17]20 have reported smoking, male gender, and longstanding RA to be risk factors for the development of ILD, other reports 13,14,16,17,19 have not shown any significant associations. In addition, genetic associations (human leukocyte antigen B40 and ␣ 1 -antitrypsin) have been described.…”
Section: Ra-ild: Epidemiology and Clinical Presentationmentioning
confidence: 86%
“…Studies [12][13][14][15][16][17][18][19] have reported a prevalence as low as 4% and as high as 68%. The majority of cases of RA-ILD occur in patients between the ages of 50 and 60 years.…”
Section: Ra-ild: Epidemiology and Clinical Presentationmentioning
confidence: 99%
“…J. Biederer et al показали ассоциацию субкли-нического течения ИПЛ при РА с рентгенотомографи-ческим признаком «матового стекла» [19]. Кроме того, B. R. Gochuico et al сообщили о прогрессировании субклинического ИПЛ у 57 % пациентов с РА, что про-явилось ухудшением рентгенотомографической карти-ны легких [10]. Однако остается неясным, является ли субклиническое течение ИПЛ при РА с картиной «ма-тового стекла» предшественником развития тяжелых фиброзных изменений легочной ткани.…”
Section: Abstract: Rheumatoid Arthritis Subclinical Interstitial Puunclassified
“…В ряде исследований установлены факторы риска развития ИПЛ при РА: серопозитивность по антите-лам к циклическому цитруллинированному пептиду (АЦЦП), курение, мужской пол, наличие других си-стемных проявлений [10,11]. Пристальное внимание исследователей в последнее время приковано к АЦЦП.…”
unclassified
“…In contrast, methotrexate, a common agent used in many CTD, has been shown to not only provide no clinical benefit in RA-ILD, but may be potentially harmful by leading to ILD disease progression (Gochuico et al, 2008). Therefore, methotrexate should not be used in the setting of RA-ILD.…”
Section: Thus W E R E C O M M E N D T H a T M Y C O P H E N O L A Tmentioning
confidence: 99%